2022
DOI: 10.1108/jrim-01-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

How social presence influences consumer purchase intention in live video commerce: the mediating role of immersive experience and the moderating role of positive emotions

Abstract: PurposeThis paper aims to examine the relationship between social presence and consumer purchase intention in the context of livestreaming commerce and test the mediating role of immersive experience and the moderating role of positive emotions.Design/methodology/approachThe authors used a convenience sampling method to select 408 college students from a university in Ganzhou as the participants. They employed structural equation modeling to test the hypotheses, as well as Hayes' PROCESS to test the mediation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 68 publications
1
21
0
3
Order By: Relevance
“…Compared to traditional e-commerce platforms, immersive technologies tend to create stronger social connectedness. Recently, there has been research on the effect of social presence on behavioral intentions within the video commerce context (Huang et al , 2022), while Liao et al (2022) explored the path from immersion to behavioral intentions within the live shopping context. Our study contributes to the interactive marketing literature by specifically exploring the mediating effects of immersion and presence.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Compared to traditional e-commerce platforms, immersive technologies tend to create stronger social connectedness. Recently, there has been research on the effect of social presence on behavioral intentions within the video commerce context (Huang et al , 2022), while Liao et al (2022) explored the path from immersion to behavioral intentions within the live shopping context. Our study contributes to the interactive marketing literature by specifically exploring the mediating effects of immersion and presence.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Customers will explore a new alternative to try if they find a website straightforward to use and navigate, boosting their chances of completing an online purchase (Islam et al, 2021). Despite the fact that people use the internet and shop online in various ways, perceived ease of use has an influence on the whole information system (Huang et al, 2022a(Huang et al, , 2022b. The perceived ease of use has a strong influence on shopping behavior when it comes to adopting information technologies (Davis, 1989).…”
Section: 32mentioning
confidence: 99%
“…Te research on user behavior of short videos mainly focuses on the use or continued use intention [3,[29][30][31][32][33], purchase intention [34][35][36][37], and other behavioral infuence of short video media [38][39][40]. It is found that perceived enjoyment, social infuence, and narcissism positively impact users' intention to use the TikTok app [29].…”
Section: User Behavior Research Related To the Short Video Appmentioning
confidence: 99%